Alcoholic Consumption of Young Italians During the SARS-CoV-2 Pandemic - Federico, Alessandro; Mazzarella, Chiara; Spina, Annamaria; Dallio, Marcello; Romeo, Mario; Masarone, Mario; Persico, Marcello; Gravina, Antonietta G.; Luzza, Francesco; Abenavoli, Ludovico; Di Mauro, Maurizio; Loguercio, Carmelina (Reviews on Recent Clinical Trials, 2022)
Background: The international health emergency caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which, at the end of 2019, hit the world, forced the governments of all countries to adopt stringent restrictive measures to contain the spread of the virus. Several studies have revealed worsening levels of anxiety, depression and perceived stress related to these restrictions and the resulting lifestyle changes. Some studies have also confirmed the presence of a relationship between SARS-CoV-2-related emotional distress and drinking behavior. Indeed, is a wellknown fact that alcohol consumption is one of the behavioral strategies used to reduce negative emotional states. However, it was documented that young people developed different responses to alcohol use during the pandemic than adults. Objective: The aim of this work was to investigate the consumption habits of young Italians and how the consumption and purchase of alcoholic beverages have changed following the pandemic. New ways of drinking alcohol were also interesting to observe, such as online. Methods: Young people between 18 and 35 years old were subjected to an anonymous questionnaire of 22 questions on the adoption of forms of behavior at risk through alcohol consumption, the quantity and occasions of preferential consumption, and on the methods and quantities of alcoholic beverage purchase, before and during the SARS-CoV-2 pandemic. The subjects who declared themselves
Keywords: social restrictions